2020
DOI: 10.1016/j.brs.2020.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial direct current stimulation combined with exercise modulates the inflammatory profile and hyperalgesic response in rats subjected to a neuropathic pain model: Long-term effects

Abstract: Background: Behavioral alterations, like mechanical and thermal hyperalgesia, and modulation of biomarkers in the peripheral and central nervous systems (CNS) are markers of chronic pain. Transcranial direct current stimulation (tDCS) with exercise is a promising therapy for pain due to its neuromodulatory capacity. Objective: To assess the individual effects of tDCS, exercise, and the two combined on the nociceptive response and BDNF, IL-1b, and IL-4 levels in the CNS structures of rats in a chronic pain mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 58 publications
3
38
1
Order By: Relevance
“…A cutoff latency of 50 s was established. Three trials were done at intervals of 20 min, and the latency (seconds) was the average of three trials ( Kooshki et al, 2020 ; Lopes et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…A cutoff latency of 50 s was established. Three trials were done at intervals of 20 min, and the latency (seconds) was the average of three trials ( Kooshki et al, 2020 ; Lopes et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study corroborates that rats subjected to chronic restraint‐induced hyperalgesia displayed analgesic response after forced swimming, as an acute stress model, but not after 3 hr restraint (Da Silva Torres et al., 2003). However, we have shown that regular aerobic treadmill exercise presents an analgesic effect in a neuropathic pain model in rats (Lopes et al., 2020). In this context, rats showed delayed hyperalgesia induced by the single exercise stress protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Sham-stimulated rats underwent similar procedures, but the stimulator was turned off throughout the experiments. 40 …”
Section: Methodsmentioning
confidence: 99%